Local Civil Society Place, Time and Boundaries - Mann, Robin (Civil Society and Social Change, 2021)
Epdf and ePUB available Open Access under CC-BY-NC licence. Drawing on place-based field investigations and new empirical analysis, this original book investigates civil society at local level. The concept of civil society is contested and multifaceted, and this text offers assessment and clarification of debates concerning the intertwining of civil society, the state and local community relations. Analysing two Welsh villages, the authors examine the importance of identity, connection with place and the impact of social and spatial boundaries on the everyday production of civil society. Bringing into focus questions of biography and temporality, the book provides an innovative account of continuities and changes within local civil society during social and economic transformation.